ANALISIS ANOMALI PASAR TERHADAP RETURN SAHAM LQ-45 DI BURSA EFEK INDONESIA : PENGUJIAN DAY OF THE WEEK EFFECT, WEEKEND EFFECT, WEEK FOUR EFFECT DAN ROGALSKY EFFECT - Ferita, Dona; Efni, Yulia i; Fitri, Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to test and analyze whether there are market anomaly (day of the week effect, weekend effect, week four effect and rogalsky effect) on stock return. The population in this study were the companies listed in the LQ-45 index during the period of January – Desember 2017.The sample selection using purposive sampling method to obtained a sample of 38 companies.The secondary data was collected such as daily stock prices from LQ-45 from January to December 2017.Hypotheses are tested by Anova, One Sample T-Test and Independent Sample T-Test SPSS version 20.All hypothetical test show that: (1) hypothese 1 tested by ANOVA show that there is no day of the week effect on LQ45 stock return in Indonesia Stock Exchange period Jnauary - December 2017. (2) hypothese 2 tested by Independent Sample T-Test show that there isno weekend effect on LQ-45 stock return in Indonesia Stock Exchange period Jnauary - December 2017. (3hypothese 3 tested by One Sample T-Test show that there is no week four effect on LQ-45 stock return in Indonesia Stock Exchange period Jnauary - December 2017. (4) hypothese 4 tested by Independent Sample T-Test show that there is no rogalsky effect on LQ-45 stock return in Indonesia Stock Exchange period Jnauary - December 2017.Keywords : Market Anomaly, Stock Return, Day of the Week Effect, Weekend Effect,Week Four Effect and Rogalsky Effect.